Faktor Demografi Sebagai Penguat Timbulnya Stres Pada Pasien Kanker - Werdani, Yesiana Dwi Wahyu; Sari, Nia Novita; Sibarani, Boy Sakti Parningotan (Fakultas Keperawatan, Universitas Katolik Widya Mandala Surabaya, 2021)
Cancer is still interpreted by most people as a disease that is difficult to cure and causes death in a short time, this triggers the psychological distress of cancer patients. The purpose of this study was to describe the demographic factors that strengthen the incidence of stress in cancer patients. The design used is descriptive design. The population of all cancer patients at Kedungdoro and Rangkah Public Health Center Surabaya, a sample of 20 people was taken by purposive sampling based on inclusion criteria. The instrument used is the Perceived Stress Scale (PSS) which has been tested for validity and reliability. The statistical test used is descriptive statistics on each of the assessed factors. The factors that strengthen the emergence of stress with the highest score on each factor are adult age (19.2 + 7.91), male gender (24.5 + 9.19), respondents who work (18.66 + 4.76), living at home with parents (21.42 + 6.97), type of breast cancer (18.69 + 7.45), duration of diagnosis of cancer 5 – 7 years (21.8 + 5.89), cancer stage 0 (21.12 + 6.79), type of chemotherapy and radiation therapy (22.5 + 7.85). Eight factors amplify the occurrence of stress with the results of the mean stress scores varying and all of them fall into the category of moderate stress. Stress does not appear with just one stressor, but a combination of multifactorials that are interrelated and trigger stress in cancer patients